PENGARUH FAKTOR MAKROEKONOMI TERHADAP RETURN HARGA SAHAM JAKARTA ISLAMIC INDEX (JII) MENGGUNAKAN METODE REGRESI DATA PANEL - Intan Salsabila; Sigit Dwi Prabowo; Fuad Muhajirin Farid (Universitas Lambung Mangkurat, 2025)
The Indonesian capital market has experienced developments that show its role as an important component in the economy. As one of the countries with a Muslim population, the Jakarta Islamic Index (JII) is used as an investment in stocks based on sharia. Every investor in the capital market, whether based on sharia or conventional, really needs relevant information about what macroeconomic factors can affect investment activities, especially on stock returns. The purpose of this study is to analyze the effect of macroeconomic factors, namely inflation, interest rates, and exchange rates on stock returns in companies listed on the Jakarta Islamic Index (JII) for the 2019-2022 period using the panel data regression analysis method. A method that is more likely to build and test more complex regression models. Based on the results of panel data regression processing, using the common effect model approach as the best model, the results of the f test showed that inflation, interest rates and exchange rates simultaneously had a significant effect on stock returns. The results of the t test also showed that inflation, interest rates, and exchange rates partially had a significant effect on stock returns.